A literature review of knowledge translation and partnership research training programs for health researchers - Hannah Tait; Anna Williamson (BMC, 2019)
Abstract Background Researchers and policy-makers are increasingly working together with the goal of creating research that is focused on solving real-world problems; however, knowledge translation (KT) activities, and the partnerships they often require, can be challenging. The aim of this review is to determine the extent of the literature on training programs designed to improve researcher competency in KT and to describe existing training methods that may be used by those hoping to build capacity for partnership research. Methods MEDLINE, EMBASE, PsycINFO and CINAHL were searched for peer review articles published between January 2000 and July 2019. Studies were eligible for inclusion in the review if they described the development of, curriculum for, or evaluation of KT and/or partnership research training programs. Data extraction included information on evaluation methods, outcomes and implications as well as the format, aims and themes of each capacity-building program. Results The review identified nine published articles that met inclusion criteria - four papers described training events, two papers described participant experiences of specific learning sessions within a larger training course, two papers described part time secondments for KT capacity-building and one paper described a plan for KT training embedded within an existing research training course. All programs were delivered face-to-face, all included practical skills-building opportunities, and all employed multiple learning modalities such as seminars and small group discussions. Evaluation of the training programs was primarily conducted through qualitative interviews or feedback surveys. Conclusion To date, few KT training initiatives have been described in the literature and none of these have been rigorously evaluated. The present review offers insights into the planning, development and participant experiences associated with the small number of training initiatives that have been described. There is insufficient evidence available at present to identify the most effective models for training researchers in KT and partnership skills.